Pengaruh Model Pembelajaran Picture and Picture Berbantuan Powtoon Terhadap Kemampuan Menulis Puisi Siswa Kelas XI SMK Muhammadiyah 2 Pekanbaru - Juliyanti, Ines; Septiyanti, Elvrin; Permatasari, Silvia (CV. Rayyan Dwi Bharata, 2025)
This study aims to examine the effect of the Picture and Picture learning model assisted by Powtoon on the poetry writing skills of 11th grade students at SMK Muhammadiyah 2 Pekanbaru. The research design used was a pretest-posttest control group design, with two groups of students: the experimental group using the Picture and Picture model assisted by Powtoon and the control group using conventional learning. The research sample consisted of 80 students selected using cluster random sampling. Data were collected through poetry writing tests at the pretest and posttest stages. Data analysis used the Mann-Whitney U test and simple linear regression. The results showed a significant increase in the experimental group, with a pretest average score of 54.38 and a posttest average score of 80.48, while the control group increased from 51.40 to 70.65. The statistical test showed a significance value of 0.002 (Sig. 0.05), which means that the Picture and Picture model assisted by Powtoon has a positive effect on students' poetry writing skills.